Employee perception of corporate social responsibility authenticity: A multilevel approach - Kim, Hyunok; Lee, Myeongju (Frontiers in Psychology, 2022)
Stakeholder interest in the accuracy of Environment Social and Governance (ESG) data and Corporate Social Responsibility (CSR) authenticity has increased, as more companies are disclosing their ESG data. Employees are one of the most important stakeholders of a company, and they have access to more CSR information than other external stakeholders. Employees have a dual role of observing and participating in CSR. Employee perceptions of CSR authenticity play a key role in the positive effects of CSR. In this study, the research model was analyzed through multilevel analysis to contribute to the literature on the mechanism by which CSR affects employees' job attitudes and perceptions of CSR authenticity. First, hypothesis testing confirmed that external CSR is positively associated with employees' perceptions of CSR authenticity. Second, CSR authenticity mediates a positive relationship between external CSR and emotional commitment. As the direct effect of external CSR on emotional commitment was not statistically significant, it could be confirmed that the full mediation relationship was significant through CSR authenticity. This study makes three theoretical contributions to the literature on employees' perceptions of CSR. First, it examines the mechanism of the impact of CSR on employees. By examining the mechanism by which employees recognize and interpret CSR, this study attempts to uncover the black box that CSR affects employees. Second, this study contributes to the literature on CSR authenticity by explaining the mediating role of CSR authenticity in the relationship between CSR and employee job attitudes through construal-level theory. Finally, this study contributes to the employee-based CSR literature by analyzing the effect of CSR as an organizational-level variable on emotional commitment as an individual-level variable through multilevel structural equation modeling (MSEM).